User Interface Design for e-Learning System - Bernard Renaldy Suteja; Agus Harjoko (Seminar Nasional Aplikasi Teknologi Informasi (SNATI), 2008)
With the demand for e-Learning steadily growing and the ongoing struggle to convince the skeptics of thepotential of e-Learning and online virtual classrooms, quality design is the foundation for a successful DEprogram. The design of the instruction and the design of the user interface are critical elements in providingquality education with a virtual, e-Learning model. This White Paper will focus on the design of the e-Learninguser interface (UI). This paper provide examples of user interface design from e-Learning prototype.Keywords: e-Learning, user interface design.